Developing BACE-1 inhibitors for FXS - Westmark, Cara J.; Berry-Kravis, Elizabeth M.; Ikonomidou, Chrysanthy; Yin, Jerry; Puglielli, Luigi (Frontiers in Cellular Neuroscience, 2013)
Fragile X syndrome (FXS) is a debilitating genetic disorder with no cure and few therapeutic options. Excessive signaling through metabotropic glutamate receptor 5 (mGluR5) in FXS leads to increased translation of numerous synaptic proteins and exaggerated long-term depression (LTD). Two of the overexpressed proteins are amyloid-beta protein precursor (APP) and its metabolite amyloid-beta (Aβ), which have been well-studied in Alzheimer’s disease (AD). Here we discus the possibility that pharmaceuticals under study for the modulation of these proteins in AD might be viable therapeutic strategies for FXS. Specifically, a recently identified acetyltransferase (ATase) inhibitor that reduces the levels and activity of β-site APP cleaving enzyme (BACE-1) has strong potential to attenuate BACE-1 activity and maintain homeostatic levels APP catabolites in FXS.